Advice-implicative actions: Using interrogatives and assessments to deliver advice in mundane conversation. (June 2015) - Shaw, Chloe; Potter, Jonathan; Hepburn, Alexa
Work on advice has concentrated on institutional settings where there are restrictions on roles, actions and their organisation. This article focuses on advice giving in mundane settings: interactions between mothers and their young-adult daughters in a corpus of 51 telephone calls. Analysis reveals a range of designs that can be 'advice implicative' including advice-implicative interrogatives and advice-implicative assessments. Recipients orient to the characteristic features these implicit forms share with more explicit advice: normative pressure on the recipient's conduct and epistemic asymmetry between advisor and advisee. Advice-implicative actions orient to contingencies on the recipient's ability or willingness to perform the target action. They also display varying degrees of entitlement over the recipient's performance of the target action. Manipulating contingency and entitlement can soften or heighten both the normative thrust and the knowledge asymmetry of the advice giving. This analysis further discusses the distinction between the practices of advising, directing and requesting, and allows consideration of how action design connects to relationality between parties.